Portable PCR field-based detection of sweetpotato viruses - Ssengo, J.; Wasswa, P.; Mukasa, S.B.; Okiror, A.; Kyamanywa, S. (African Crop Science Journal, 2020)
Sweetpotato (Ipomoea batatas Lam.) production is greatly constrained by viral infections, especially Sweet potato feathery mottle virus and Sweet potato chlorotic stunt virus that synergistically cause a severe sweetpotato virus disease. The impact of viruses is aggravated by the vegetative nature of the crop and inaccessibility to dependable diagnostic tools in rural areas where sweetpotato production is done. This makes it hard for seed inspectors to perform quality checks prior to use of vines for planting. The objective of this study was to develop a procedure that allows for detection of sweetpotato viruses on-site. This involved modification of the Lodhi et al. (1994) nucleic acid extraction procedure, by omitting some of the laboratory specific steps and varying the incubation time in liquid nitrogen, instead of the freezer. Incubation in liquid nitrogen for only 1.5 hours yielded as high quality RNA compared to that of the original protocol, when incubation was done at 4°C overnight in a freezer. Reverse transcriptase (RT) was run using a portable miniPCR thermocycler; and the resulting cDNA was amplified using this miniPCR machine instead of using a laboratory stationed conventional PCR thermocycler. The cDNA was efficiently amplified and amplicons were similar to those obtained with the original extraction protocol and subsequent amplification by the conventional RT-PCR. Our protocol reduced extraction time from about 16 hours for the original protocol, to about 2 hours and 45 minutes. If this tool is utilised by the crop protection departments, we believe it will contribute greatly towards sustainable sweetpotato production through making timely recommendations.
Keywords: Incubation; Liquid nitrogen; MiniPCR